2011
DOI: 10.1002/jsfa.4748
|View full text |Cite
|
Sign up to set email alerts
|

Color compensation in nitrite‐reduced meat batters incorporating paprika or tomato paste

Abstract: Color characteristics-instrumental and sensory-in these kinds of meat products were enhanced by the addition of 2.5-3.0% of tomato paste, presenting results close to the non-reduced nitrite control. Similarly, antioxidant components of tomato paste or paprika reduced lipid oxidation. Nitrite reduction from 150 to 100 ppm could be achieved employing tomato paste as a natural pigment to improve color and texture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 46 publications
(58 reference statements)
1
23
0
1
Order By: Relevance
“…The EU Directive 2006/52/EC, refers to the necessity of reducing the use of nitrites (EC, 2006) in organic meat industry. Therefore, alternative procedures for meat curing are required to produce organic processed meats safety with ensured similar to cured meat colour (B azan-Lugo, García-Martínez, Alfaro-Rodríguez, & Totosaus, 2012;Sebranek & Bacus, 2007). Numerous studies have been carried out to replace nitrite in meat products (Hayes, Canonico, & Allen, 2013;Morita et al, 1996;Sebranek, JacksonDavis, Myers, & Lavieri, 2012;W ojciak, Karwowska, & Dolatowski, 2014;W ojciak, Dolatowski, & Koło _ zyn-Krajewska, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The EU Directive 2006/52/EC, refers to the necessity of reducing the use of nitrites (EC, 2006) in organic meat industry. Therefore, alternative procedures for meat curing are required to produce organic processed meats safety with ensured similar to cured meat colour (B azan-Lugo, García-Martínez, Alfaro-Rodríguez, & Totosaus, 2012;Sebranek & Bacus, 2007). Numerous studies have been carried out to replace nitrite in meat products (Hayes, Canonico, & Allen, 2013;Morita et al, 1996;Sebranek, JacksonDavis, Myers, & Lavieri, 2012;W ojciak, Karwowska, & Dolatowski, 2014;W ojciak, Dolatowski, & Koło _ zyn-Krajewska, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of hue angle was in contrast with the conclusion in a* values which mentioned above. Bázan‐Lugo, García‐Martínez, Alfaro‐Rodríguez, and Totosaus () studied the pork meat batters incorporated with paprika and tomato paste which showed the samples with higher a* values had lower hue angle scores.…”
Section: Resultsmentioning
confidence: 99%
“…(). This difference might be the result of the addition of paprika oleoresin, which has been shown to be an inhibitor of lipid oxidation in meat products (Bázan‐Lugo et al., ). Similar results were also reported by Huang, Xiong, Kong, Huang, and Li () who found that frozen pork dumpling stored at −7°C had significantly higher amounts of TBARS than those stored at −18°C and those with fluctuation between −7 and −18°C ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…They are usually based on the use of nitrate-containing plant material, such as celery powder (Terns et al, 2011), which is of course a pseudosolution. Other approaches are based on the substitution of the effects of curing agents by other biological substances, as for the use of antimicrobial cherry powder , rosemary extract as a colour-stabilizing antioxidant , or natural colourants such as curcumin, paprika, β-carotene, cochineal, and tomato (Bázan-Lugo et al, 2012). In addition, two promising enzymatic processes are being explored that may offer an alternative for cured colour formation in meat products; namely, the formation of zinc protoporphyrin IX by ferrochelatase or mitochondrial enzymes, as described for Parma ham (Wakamatsu et al, 2009), and the formation of nitrosomyoglobin by meat-associated bacteria with NOS activity (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%